Odpowiedzi

  • Roma
  • Community Manager
2010-02-11T16:29:12+01:00
A)
2(3a + 4b) + 5(a + 2b) = 6a + 8b + 5a + 10b = 11a + 18b

b)
25(4a + 12b) - 15(6a - 8b) = 100a + 300b - 90a +120b = 10a + 420b

c)
3(a + b) + 5(a - b) - 2(4a - b) = 3a + 3b + 5a - 5b - 8a + 2b = 0

d)
½(2a - 4b) + ⅓(3a + 9b) = a - 2b + a + 3b = 2a + b

e)
¾(a - b) - ⅛(a + b) = ¾a - ¾ - ⅛a - ⅛b = ⁶/₈a - ⁶/₈b - ⅛a - ⅛b = ⅝a - ⅞b

f)
0,1(4a - 5b) - 0,2(3a + 4b) = 0,4a - 0,5b - 0,6a - 0,8b = - 0,2a - 1,3b

g)
1,1(1,1a - 1,2b) + 1,2(1,2 + 1,1) = 1,21a - 1,32b + 1,2* 2,3 = 1,21a - 1,32b + 2,76

Jednak wydaje mi się, że zapomniałaś w ostatnim nawiasie wpisać a i b i wtedy byłby taki wynik:
1,1(1,1a - 1,2b) + 1,2(1,2a + 1,1b) = 1,21a - 1,32b + 1,44a + 1,32b = 2,65a
2010-02-11T16:29:38+01:00
A)6a+8b+5a+10b=11a+18b
b)100a+300b-90a-120b=10a+180b
c)3a+3b+5a-5b-8a-2b=-4b
d)a-2b+a+3b=b
e)0,75a-0,75b-0,125a+0,125b=0,625a+0,625b
f)4a-5b-6a+8b=-2a3b
g)1,21a-1,32b+1,44+1,32=1,21a-1,32b+2,76